2001
DOI: 10.3171/jns.2001.95.3.0480
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased phosphatidylinositol 3-kinase signaling with increased invasiveness and gelatinase activity in malignant gliomas

Abstract: The increase in p-Akt staining within these PTEN-deficient gliomas is consistent with what would be predicted from unchecked PI 3-K signaling. Furthermore, the immunohistochemically detected colocalization of p-Akt and MMP-2 and MMP-9 supports the authors' in vitro studies and the proposed linkage between PI 3-K signaling and MMP activity in gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 49 publications
10
65
0
Order By: Relevance
“…Several in vitro and in vivo experiments with glioblastoma corroborate these results. 20,21,30,31 For instance, our proliferation data are similar to results by Su et al, where dosing orthotopic mouse xenografts with LY294002 resulted in *40% inhibition of glioblastoma growth compared with controls after 5 days. The similarity in results is somewhat surprising as Su et al utilized a repeated dosing regimen compared with the static nonrenewal exposure in our experiment.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325supporting
confidence: 89%
See 1 more Smart Citation
“…Several in vitro and in vivo experiments with glioblastoma corroborate these results. 20,21,30,31 For instance, our proliferation data are similar to results by Su et al, where dosing orthotopic mouse xenografts with LY294002 resulted in *40% inhibition of glioblastoma growth compared with controls after 5 days. The similarity in results is somewhat surprising as Su et al utilized a repeated dosing regimen compared with the static nonrenewal exposure in our experiment.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325supporting
confidence: 89%
“…[34][35][36] PTEN dephosphorylates phosphatidylinositol (3,4,5)-trisphosphate (PtdIns (3,4,5)-P 3 )-mediated activation of serine/threonine kinase (AKT), thereby controlling cell proliferation, survival, migration, and invasion. 22,30,37 Inhibiting PI 3-kinase activity with LY294002 decreases glioblastoma proliferation, migration, and invasion by mitigating enhanced AKT phosphorylation.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325mentioning
confidence: 99%
“…In vitro studies with glioma cell lines deficient in PTEN expression showed that inhibitors of PI3K (LY294002 and wortmannin), or overexpression of PTEN, reduced cell invasiveness in vitro, and this was associated with reduced activity of matrix metalloproteinases including MMP2 and MMP9 (Kubiatowski et al, 2001;Koul et al, 2001).…”
Section: Migration and Invasionmentioning
confidence: 99%
“…18 Another study has reported that the increased invasiveness and gelatinase activity in C6 glioma cells are associated with the increase of PI3-K activity, an important downstream signaling target of EGFR, as demonstrated by LY294002, a specific PI3-K inhibitor, can inhibit the activation of Akt, expression of MMPS and the cell invasion in C6 glioma cells. 29 An U6 promoter-based RNAi gene therapy targeting PI3-K b110 subunit can inhibit U251 growth, induce apoptosis, G2/M cell cycle arrest and suppress tumor cell invasion (unpublished date). Thus, signal transduction pathways downstream of EGFR have been found to be critical in mediating important cellular functions, including survival, proliferation, migration, and invasion; inhibition of overexpressed and/or activated EGFR/PI3-K-mediated signaling pathways possess great significance in malignant glioma gene therapy.…”
Section: Biological Changes By Silenced Egfr Expressionmentioning
confidence: 99%